PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS DAN DANA BAGI HASIL TERHADAP BELANJA MODAL (Studi Empiris Pada Pemerintah Kabupaten / Kota Di Provinsi Sumatera Barat Periode 2011 - 2014) - Said Ridho Fadillah; Enni Savitri; Rofika Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to test empirically the influence of Local Revenue, General Allocation Funds, Special Allocation Funds, and the Revenue Sharing Funds to Capital Expenditures. The population used in this study is the Regional Government of West Sumatra Province. With 12 districts / municipal being sampled. The sampling technique is Purposive Sampling. Data collection was carried out from the Local Budget (APBD) Realization Report from 2011 to 2014, obtained from the Directorate General of Fiscal Balance of Regional Government. The method of analysis in this study using multiple linear regression method with SPSS version 21. The results of this study prove that the local revenue has no effect on capital expenditure, this is because PAD is more widely used to finance routine / operational expenditure. General allocation funds have no effect on capital expenditures, because DAU is a block grant whose use is handed over to regions in accordance with local priorities and needs. Special allocation funds have a positive effect on capital expenditure, because DAK is specific purpose grant in accordance with national priorities. Revenue-sharing funds have a positive effect on capital expenditure, because DBH is used for the development of regional facilities and infrastructure.Keyword : Local Revenue, General Allocation Fund, Special Allocation Fund, Revenue Sharing Fund, Capital Expenditure